Produtividade em espécies de Drosophila do subgrupo saltans (grupo saltans, subgênero Sophophora): efeitos da infecção por Wolbachia em linhagens normais e introgredidas - Patarro, Thais de França [UNESP] (2015)
Reproductive isolation mechanisms are agents that prevent or decrease the exchange of genes between species or populations of the same species that are in process of speciation. These mechanisms are comprised of a series of processes operating at different levels of reproduction, ranging from pre-zygotic to post-zygotic barriers. In recent decades, studies have indicated that the absence of progeny can also be promoted by interactions of symbiont microorganisms and their hosts. Presently, the most known endosymbionts capable of interact with the insects, interfering in the reproductive process, are the alphaproteobacteria of the genus Wolbachia. In the present study, we investigated the Wolbachia effects on reproduction, focusing the parameter productivity (number of progeny) in crosses involving four strains of Drosophila saltans and D. prosaltans (close species belonging to the saltans group, Sophophora subgenus) and two introgressed strains started with F1 hybrids of these two species. Preliminary tests for screening Wolbachia showed that each of the six strains was infected with one strain of the symbiont. The results on productivity were obtained from intra and intercrosses of the strains in the conditions infected or uninfected. The elimination of Wolbachia was performed by treatment of the strains with the antibiotics tetracycline. The main mechanism resulting from the interaction symbiont-host described in the literature is called cytoplasmatic incompatibility (CI) and occurs in the intercrosses of uninfected females with infected males. It is considered that, in infected males, there are changes in the sperm that only the oocytes of infected females are able to correct, reestablishing the productivity. The present results on Wolbachia infection of the species from the saltans group were variable. In several crosses of the strains, the combinations that are sterile or almost sterile when CI effect occurs, were the most productive ...